Community engagement to tackle terrorism and violent extremism: challenges, tensions and pitfalls - Cherney, Adrian (Policing and society, 2017)
It is recognised that community cooperation is central to mitigating the risks of terrorism. This has seen police and security agencies in western jurisdictions engage Muslim communities in an effort to improve intelligence gathering and threats arising from violent extremism. However, community engagement in the context of counter-terrorism is fraught with tension, which makes it a challenging and at times conflict-laden process. This paper explores these tensions highlighting the challenges police and Muslims face when working in partnership. We focus on four key issues: (1) overcoming distrust and generating trust; (2) balancing the priorities of intelligence gathering, community engagement and trust building; (3) choosing partners and distinguishing between friend and foe, and (4) levels of consultation and community input. We argue that community-based counter-terrorism requires new ways of thinking about how engagement is best facilitated and sustained. The paper draws on the international literature and the authors own experience with engagement and partnership work with Australian Muslim communities and police. Lessons for counter-terrorism policing are highlighted.